La familia homoparental en función de la sentencia nro. 184-2018-sep-cc y las consecuencias jurídicas en los derechos de los menores - Nancy Brigitt, Montero Chauca (2019)
Nowadays, the family is one of the oldest social institutions which remains even in the present; it is recognized and guaranteed in article sixty-seven of the Constitution of the Republic of Ecuador. It mentions that the family is the fundamental nucleus of society; at the same time, this article recognizes the different kinds of family. According to the above mentioned, it concludes that the family can be formed in different ways, not only from the marriage between a man and a woman. They join their lives for child-bearing and helping each other, since this union, as is established in the article sixty- eight of the constitutional text. It also could be between two men or two women, who can form a common-law relationship among other kinds of family. The proposal for this investigation is analyzing the legal phenomena related to homo-parental families. The same ones were recognized in the Judgment of the Constitutional Court No. 184-18-SEP-CC within the case called “Satya,” dated May 29,2018. Where for the first time, it was legally admitted that her two mothers legally recognize a child, originating homo- parental families, that is, those that are formed by same genre couples with children. Because of this, the current investigation is trying to identify whether or not the recognition of double maternity or paternity in Ecuador violates the children’s and adolescents’ rights who belong to these new kinds of family, in particular to the identity right. This situation has not been analyzed yet from the academy and is being exposed to this work.